Effect of long-term cannabidiol on learning and anxiety in a female Alzheimer’s disease mouse model - Chesworth, Rose; Cheng, David; Staub, Chloe; Karl, Tim (Frontiers in Pharmacology, 2022)
Cannabidiol is a promising potential therapeutic for neurodegenerative diseases, including Alzheimer’s disease (AD). Our laboratory has shown that oral CBD treatment prevents cognitive impairment in a male genetic mouse model of AD, the amyloid precursor protein 1 x presenilin 1 hemizygous (APPxPS1) mouse. However, as sex differences are evident in clinical populations and in AD mouse models, we tested the preventative potential of CBD therapy in female APPxPS1 mice. In this study, 2.5-month-old female wildtype-like (WT) and APPxPS1 mice were fed 20 mg/kg CBD or vehicle via gel pellets daily for 8 months and tested at 10.5 months in behavioural paradigms relevant to cognition (fear conditioning, FC; cheeseboard, CB; novel object recognition, NORT) and anxiety-like behaviours (elevated plus maze, EPM). In the CB, CBD reduced latencies to find a food reward in APPxPS1 mice, compared to vehicle-treated APPxPS1 controls, and this treatment effect was not evident in WT mice. CBD also increased speed early in the acquisition of the CB task in APPxPS1 mice. In the EPM, CBD increased locomotion in APPxPS1 mice, but not WT mice, with no effects of CBD on anxiety-like behaviour. CBD had limited effects on the expression of fear memory. These results indicate preventative CBD treatment can have a moderate spatial learning-enhancing effect in a female amyloid-β based-AD mouse model. This suggests CBD may have some preventative therapeutic potential in female familial AD patients.